Analisis Isu Etika Data Pribadi Dalam Sistem Informasi Pendidikan - Zahra Auliya Febbyanti; Ni Putu Devita Natalia Putri; Naisylla Anastasya Irawan; Indriyani (Yayasan Al-Afif, 2026)
The development of educational information systems has increased the use of personal data, including student and educator information. While improving data management efficiency, this development also raises various ethical issues related to privacy and information security. This study aims to analyze ethical issues of personal data in educational information systems and their impact on user privacy and information security. A qualitative approach through a literature review of relevant studies and regulations was used in this research. The results indicate that the main issues include a lack of transparency in data management, risks of information leakage, and potential misuse of personal data, which may lead to privacy violations and reduced user trust in the system. Therefore, the implementation of ethical principles, improved system security, and comprehensive data protection policies are necessary to ensure privacy and information security